2018
DOI: 10.1080/14767058.2018.1432589
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of the fetal occiput-spine angle during the first stage of labor as predictor of the progress and outcome of labor

Abstract: There was a significantly longer duration of both first and second stages of labor with higher rates of CS and maternal and fetal complications in women with OSA <126.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
10
1
5

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(18 citation statements)
references
References 9 publications
2
10
1
5
Order By: Relevance
“…This cutoff is similar, but slight lower, that that reported by Maged et al, who reported a cut-off value of 126°. 5 Ghi et al reported a cut-off of 125°, which is again greater than the value obtained in our study. 4 The differences between our study and those of Maged et al and Ghi et al may be attributed to the differences in the study populations of the studies.…”
Section: Discussioncontrasting
confidence: 93%
See 3 more Smart Citations
“…This cutoff is similar, but slight lower, that that reported by Maged et al, who reported a cut-off value of 126°. 5 Ghi et al reported a cut-off of 125°, which is again greater than the value obtained in our study. 4 The differences between our study and those of Maged et al and Ghi et al may be attributed to the differences in the study populations of the studies.…”
Section: Discussioncontrasting
confidence: 93%
“…4 The differences between our study and those of Maged et al and Ghi et al may be attributed to the differences in the study populations of the studies. 4,5 Both studies were inclusive of both multiparas as well as nulliparas, whereas ours was restricted to nulliparas since they were the focus group of the current study.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…When combining both HPD and AOP for the prediction of the mode of birth, the assessment of both parameters has a high sensitivity of 97.7% and a high positive predictive value of 86.63% 6 Mukdee, Suntharasaj [ 28 ] 2021 Thailand 330 2D transabdominal ultrasound Active phase The sensitivity of an OSA ≥ 100 degrees for predicting vaginal birth is 83.7%, but its specificity is only 17.1%. The combination of an OSA ≥ 100 degrees with multiparity and no induction of labor can predict vaginal birth with a positive likelihood ratio of 3.6 7 Fahmy, Elhalaby [ 29 ] 2020 Egypt 70 nulliparous 2D Transperineal ultrasound Active phase VE, HPD [≥ 120 degrees] and AOP [≤ 45 mm] are significantly correlated with one another and prediction of the occurrence of normal vaginal birth 8 Kandil, Elhalaby [ 30 ] 2020 Egypt 80 2D Transperineal ultrasound Active phase The sensitivity of an AOP > 104 degrees for predicting vaginal delivery is 90%, and the specificity is 86% 9 Solaiman, Atwa [ 31 ] 2020 Egypt 28 2D Transperineal ultrasound Prolonged active phase of first or second stage s of labor Using a cut off value of 115 degrees for the AOP, the positive predictive value [PPV] of vaginal birth is 87%; using a cut off value of 42 mm for HPD results in a PPV for vaginal birth of 85% 10 Maged, Soliman [ 14 ] 2019 Egypt 400 2D Transabdominal ultrasound Active phase An OSA < 126 degrees has a sensitivity, specificity, and accuracy of 82%, 64.6%, and 92% in the prediction of the mode of birth, respectively …”
Section: Resultsmentioning
confidence: 99%